Indirect Basal Metabolism Estimation in Tailoring Recombinant Human TSH Administration in Patients Affected by Differentiated Thyroid Cancer: A Hypothesis-Generating Study - Barnabei, Agnese; Strigari, Lidia; Persichetti, Agnese; Baldelli, Roberto; Rizza, Laura; Annoscia, Claudia; Lauretta, Rosa; Cigliana, Giovanni; Barba, Maddalena; De Leo, Aurora; Appetecchia, Marialuisa; Torino, Francesco (Frontiers in Endocrinology, 2018)
Purpose. rhTSH is currently used in follow-up of patients affected by differentiated thyroid cancer. Age, sex, weight, BMI, body surface area and renal function are known factors affecting serum TSH peak levels, but the proper rhTSH dose to deliver to single patient remains elusive. In this study, the correlations of basal metabolic rates with serum TSH peak following rhTSH administration were investigated. Methods. We evaluated 221 patients affected by thyroid cancer that received a standard dose rhTSH. Blood samples were collected at pre-established time points. Data on body weight, height, and body surface area were collected. The Mifflin-St Jeor and Fleisch equations were used to assess basal metabolism. Results. The median value (range) of serum TSH peaks was 142±53 μU/ml. Serum TSH peaks were significantly lower in males than in females (p=0.04). TSH values also increased with age. Data showed a significant decrease of TSH peak levels at day 3 from the administration of rhTSH when basal metabolic rates increased (p=0.002 and p=0.009, respectively). Similar findings were observed at the day 5 (p=0.004 and p=0.04 respectively). A multivariate analysis of several factors revealed that patients’ basal metabolism (obtained using the Mifflin-St Jeor but not Fleisch equation) predicts serum TSH level peak at day 3 (p<0.001). These results were used to generate a new formula based on Mifflin-StJeor equation which reveals as a promising tool in tailoring rhTSH dose. Conclusions. Basal metabolism appears an improving factor in tailoring diagnostic rhTSH dose in patients affected by differentiated thyroid cancer.